Bioactivities of extracts, debromolaurinterol and fucosterol from macroalgae species - Begum, Sartaz; Nyandoro, Stephen S.; Buriyo, Amelia S.; Makangara, John J.; Munissi, Joan J. E.; Duffy, Sandra; Avery, Vicky M.; Erdelyi, Mate (Tanzania Journal of Science, 2018)
Parasitic diseases including malaria, and other numerous microbial infections and physiological diseases are threatening the global population. Tanzanian coast shores are endowed with a variety of macroalgae (seaweeds), hitherto unsystematically explored to establish their biomedical potentials. Thus, antiplasmodial activity using malarial imaging assay, antimicrobial activity using microplate dilution technique, antioxidant activity using DPPH radical scavenging method and cytotoxicity using brine shrimp test were carried out on crude extracts from the selected species of algae (Acanthophora spicifera, Cystoseira myrica, Cystoseira trinodis, Laurencia filiformis, Padina boryana, Sargassum oligocystum, Turbinaria crateriformis, Ulva fasciata and Ulva reticulata) occurring along the coast of Tanzania. The extracts showed antimicrobial activities with MIC ranging from 0.3- 5.0 µg/mL against Staphylococcus aureus, Streptococcus pyogenes, Pseudomonas aeruginosa, Escherichia coli, Candida albicans and Cryptococcus neoformans; DPPH radical scavenging activity at EC50 1.0- 100 µg/mL and cytotoxicity on brine shrimp larvae with LC50 value ranging from20 - 1000 µg/mL. The extracts from C. myrica and P. boryana inhibited growth of Plasmodium falciparum (3D7 strain) by 80 and 71%, respectively at 40 µg/mL while a sesquiterpene debromolaurinterol (1) which was chromatographically isolated from C. myrica exhibited antiplasmodial activity with IC50 20 µM whereas a sterol fucosterol (2) from P. boryana showed weak activity at 40 µM. Bioactivities portrayed by the investigated extracts indicate their ingredients as potential sources of bioactive agents that warrant further explorations.